Otoritas Mahkamah Syar'iyah di Aceh dalam Eksekusi Jaminan Fidusia Berdasarkan Putusan Mahkamah Konstitusi Pasca Penegsahan Qanun No 11 Tahun 2018 Lembaga Keuangan Syariah di Aceh - Afri Hasni Putra (Fakultas Syariah UIN Prof. K.H. Saifuddin Zuhri, 2023)
Sharia Economic Disputes in Aceh Province after the enactment of regulation No. 11 of 2018 concerning Sharia Financial Institutions are increasing. Fiduciary Guarantee as one of the guarantees in the form of a murabahah agreement contract between Islamic financial institutions and customers is also often colored by disputes in Aceh, the increasing number of disputes in the form of fiduciary guarantees increasingly makes the Syar'iyah Court of Absolute competence has a big role and responsibility in adjudicating sharia economic disputes in Aceh. This study aims to determine the authority of the Syar'iyah Court in Aceh in adjudicating and deciding various Sharia Economic dispute issues in Aceh as well as the factors that cause customers to dispute and Islamic financial institutions to seize collateral both through litigation and non-litigation channels. This research method uses a form of qualitative research with case study research techniques. The types of data collected are primary and secondary data. The findings are for the government and Islamic Financial Institutions to mitigate more quickly related to potential sharia economic disputes and the Syar'iyah Court has the authority to execute fiduciary guarantees by means of creditors making applications to local courts.